EVA SEBAGAI MEDIASI TERHADAP NILAI PERUSAHAAN DENGAN KEPUTUSAN KEUANGAN - Wijanti, Ni Wayan Nurani; Sedana, Ida Bagus Panji; Purbawangsa, Ida Bagus Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.11.TAHUN 2016, 2016)
Increase in the value a company has often linked to shareholder wellfare as a result of company performance. One of company performance which is financial performance can be seen as economic value added (EVA). EVA is predicted as a variable that can mediating investment opportunity, leverage, and dividend policy in influencing company value with the help of path analysis. This research used cencus of manufacturing companies listed in Bursa Efek Indonesia (BEI) that sharing its dividend troughout time window 2010 until 2013. As result of this research state, EVA only can mediating leverage influence to company value. Likewise, on examination of variable direct effect is founded only leverage that can influence directly to company value.
Keywords: Investment Opportunity, Leverage, Dividend Policy, Company Value